Model Pengelolaan Pendidikan Multikulkural di Pondok Pesantren Tradisional dan Modern - Arief Efendi (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2017)
This study aimed to describe the management model of multicultural education in traditional and modern boarding school in maintaining harmony heterogeneity students. This type of research is a qualitative study using a naturalistic approach. Subjects in this study were caregivers, teachers, traditional and modern pesantren students at two boarding schools are boarding Sunan Pandanaran Yogyakarta and modern cottage Al-barakah Nganjuk East Java. namely data collection techniques interviews, observations and document research. The results of this study: first, the model of multicultural education in the form of a traditional boarding school, namely a) the use of Indonesian as the unifying language students in learning activities and daily activities; b) intermingling of students as a vehicle to learn to live in diversity, to build mutual trust, mutual understanding and mutual respec; c) the appreciation of multicultural education in a variety of activities: the use of batik regional origin of students; activities miss the archipelago and fashion show